Credit hell : - Dvorkin, Howard S. (John Wiley & Sons, 2005)
Assessing the state of your finances, what to do about your debts, debts that deserve special attention, using credit responsibly, credit reporting agencies, credit reports & credit scores, rebuilding your credit history and your financial future, your money rights,appendix A: Budgeting worksheet, appendix B: Your household budget, appendix C: Helpful resources, appendix D: About Consolidated Credit Counseling Services, Inc.